Popyt na ubezpieczenia życiowe w aspekcie wybranych cech demograficznych i socjoekonomicznych - Dembowska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper based on the research conducted in 2003 among students of extension and evening courses in non-public schools in the region of Łódź. This article presents microeconomic analysis of life insurance demand. There is an analysis of influence of some of socioeconomic and demographic factors to buying life insurance products. The main tool used to in this article is independent test based on x2-statistic. The analysis pointed that age, sex, legal status, residence, source of income and economical situation of household decided about having life insurance products. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 138-144